BENTUK PAKAIAN ADAT BUNDO KANDUANG DI BATIPUAH BARUAH TANAH DATAR - Srimutia Elpalina; Agustina Agustina; Christanto Syam; Adek Cerah Kurnia Azis; Fitrah Cyntha Dirna; Yudhistira Oscar Olendo (Gorga : Jurnal Seni Rupa, 2023)
Clothing can be categorized into several types, such as everyday wear, workwear, festive attire, and traditional costumes. Everyday wear is used for daily activities at home or in society. Workwear is worn when someone is working, like teacher's attire or office clothing. Festive attire is specifically for celebration events, such as birthdays or weddings. On the other hand, traditional costumes are worn during customary ceremonies and hold sacred values. The traditional costume of "bundo kanduang" in Minangkabau carries philosophical and cultural significance for the community. It represents the position and role of a "bundo kanduang" in the Minangkabau traditional society. A "bundo kanduang" is an esteemed woman within a clan, responsible for domestic affairs in the community. The term "bundo kanduang" is often used as a synonym for women, yet its interpretation varies in the society of West Sumatra. There are three versions of the term: the story of "kaba" the perspective of women in West Sumatra, and the view of the Minangkabau traditional community. The traditional costume of "bundo kanduang" in Minangkabau has distinctive elements, such as "tingkuluak" (headpiece), "baju kuruang basiba" (upper garment), "kodek" (skirt), "salempang" (sash), jewelry, and footwear. Each part of the attire symbolizes specific meanings and signifies the role and responsibility of a "bundo kanduang" within her community. This research employs a qualitative descriptive method through observation, interviews, and documentation. The findings indicate that the traditional costume of "bundo kanduang" in Batipuah Baruah, Tanah Datar, possesses unique characteristics and profound cultural significance in Minangkabau's heritage. In conclusion, the preservation of the traditional costume of "bundo kanduang" is vital to safeguard the cultural richness of Minangkabau. With the passage of time, changes in the form of traditional attire can alter the meanings and symbols embedded within it. Therefore, documenting and inventorying the forms of traditional clothing is crucial for understanding and preserving this cultural heritage.Keywords: shapes, traditional clothes, bundo kanduang, women. AbstrakPakaian memiliki beberapa kategori, seperti pakaian sehari-hari, pakaian kerja, pakaian pesta, dan pakaian adat. Pakaian sehari-hari digunakan dalam aktivitas sehari-hari di rumah atau di tengah masyarakat. Pakaian kerja dipakai ketika seseorang sedang bekerja, seperti pakaian guru atau pakaian kantor. Pakaian pesta adalah pakaian khusus untuk acara perayaan, seperti ulang tahun atau pernikahan. Sedangkan pakaian adat adalah pakaian tradisional yang dipakai dalam upacara adat dan memiliki nilai sakral. Pakaian adat bundo kanduang di Minangkabau memiliki makna filosofi dan nilai budaya masyarakat yang mengenakannya. Pakaian ini menggambarkan posisi dan peran seorang bundo kanduang dalam masyarakat adat Minangkabau. Bundo kanduang adalah seorang wanita yang dituakan dalam suatu suku, yang memegang pimpinan urusan domestik dari suatu kaum dalam lingkungan masyarakat adat. Istilah bundo kanduang sering digunakan sebagai kata ganti untuk kaum wanita, namun pengertian bundo kanduang dalam masyarakat Sumatera Barat bervariasi. Terdapat tiga versi istilah bundo kanduang, yaitu versi cerita kaba, versi kaum wanita Sumatera Barat, dan versi masyarakat adat Minangkabau. Pakaian adat bundo kanduang di Minangkabau memiliki bentuk yang khas, seperti tingkuluak, baju kuruang basiba, kodek, salempang, perhiasan, dan alas kaki. Setiap bagian pakaian memiliki simbol dan makna tertentu yang menggambarkan peran dan tanggung jawab seorang bundo kanduang dalam kaumnya. Penelitian ini menggunakan metode kualitatif deskriptif dengan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pakaian adat bundo kanduang di Batipuah Baruah, Tanah Datar memiliki karakteristik yang unik dan memiliki makna mendalam dalam budaya Minangkabau. Kesimpulannya, pelestarian pakaian adat bundo kanduang penting untuk menjaga kekayaan budaya Minangkabau.Kata Kunci: bentuk, pakaian adat, bundo kanduang, perempuan. Authors:Srimutia Elpalina : Universitas Negeri PadangAgustina : Universitas Negeri PadangChristanto Syam : Universitas TanjungpuraAdek Cerah Kurnia Azis : Universitas Negeri MedanFitrah Cyntha Dirna : Sekolah Menengah Atas Negeri 2 Indralaya UtaraYudhistira Oscar Olendo : Universitas TanjungpuraReferences:Amir, M. S. (2007). Masyarakat Adat Minangkabau Terancam Punah. Jakarta: PT. Mutiara Sumber Widya.Amrida, A. (2012). œBentuk Pakaian Adat Bundo Kanduang di Batipuah Baruah Tanah Datar. Hasil Wawancara Pribadi: 5 November 2012. Tanah Datar.Anwar, R., Sastra, A. I., & Zebua, E. (2019). Pakaian Pangulu di Nagari Gunuang Kota Padangpanjang Provinsi Sumatera Barat. Gorga: Jurnal Seni Rupa, 8(2), 332-336.Azis, A. C. K., Lubis, S. K., Kartono, G., & Daulay, M. A. J. (2023). Digitalisation of Teaching Materials for Toba Batak Ethnic Decorative Variety with Procreate Media Based on p-Books and e-Books. Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 9(3), 782-793.Chaer, Abdul/ (199)). Pengantar Semanti Bahasa Indonesia. Jakarta: Rineka Cipta.Couto, Nashbary. (2009). Seni Rupa Teori dan Aplikasi. Padang: UNP Press.Dahrizal, Musra (Mak Katik). (2012). œBentuk Pakaian Adat Bundo Kanduang di Batipuah Baruah Tanah Datar. Hasil Wawancara Pribadi: 1 Desember 2012. Kota Padang.Daryusti, D. (2006). Hegomoni Penghulu dan Perspentif Budaya. Jakarta: Penerbit Pustaka.Efi, Agusti. (2006) Benda Budaya Alat Kebesaran Minangkabau: Lambang dan Makna. Disertasi. Tidak diterbitkan.Elpalina, S., Agustina, A., Azis, A. C. K., & Syukri, A. Bentuk Pakaian Adat Panghulu Di Batipuah Baruah Tanah Datar. Gorga: Jurnal Seni Rupa, 12(1), 167-173.Hakimy, Idrus. (2001). Rangkaian Mustika Adat Basandi Syarak di Minangkabau. Bandung: PT. Remaja Rosdakarya.Naim, Mochtar. (2006). Tiga Menguak Tabir: Perempuan Minangkabau di Persimpangan Jalan. Jakarta: Hasanah.Nurhaida. (2012). œBentuk Pakaian Adat Bundo Kanduang di Batipuah Baruah Tanah Datar. Hasil Wawancara Pribadi: 5 November 2012. Tanah Datar.Putra, Z. A. W., Olendo, Y. O., & Sagala, M. D. (2023). Kajian Kritik Seni: Transformasi Bentuk Penyajian Musik Tradisional Krumpyung Kulon Progo di Era Multimedia. Jurnal Sendratasik, 12(2), 146-156.